2021
DOI: 10.7759/cureus.16187
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Site Infection Post-appendectomy in a Tertiary Hospital, Jeddah, Saudi Arabia

Abstract: Background and purpose: Appendectomy considered at the top of emergency surgical procedures worldwide, and surgical site infection (SSI) is not an uncommon complication postoperatively. Many factors may be contributed to SSI occurrence; either during preoperative, intraoperative, or postoperative periods. No recent studies focusing on SSI post-appendectomy and the related factors in our region. So, we aim to find the prevalence and detect the factors that may lead to SSI in post-appendectomy patients at King A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Those who undergo laparotomy have three times the risk of SSI compared to laparoscopic appendectomy. Similar findings were reported in a local study in Saudi Arabia, which found that SSI had significantly higher odds among laparotomy patients (OR=4.11) [ 12 ]. Furthermore, a systematic review found that the pooled SSI incidence was 17.9/100 open laparotomies compared to 8.8/100 laparoscopic appendectomies [ 7 ].…”
Section: Discussionsupporting
confidence: 89%
“…Those who undergo laparotomy have three times the risk of SSI compared to laparoscopic appendectomy. Similar findings were reported in a local study in Saudi Arabia, which found that SSI had significantly higher odds among laparotomy patients (OR=4.11) [ 12 ]. Furthermore, a systematic review found that the pooled SSI incidence was 17.9/100 open laparotomies compared to 8.8/100 laparoscopic appendectomies [ 7 ].…”
Section: Discussionsupporting
confidence: 89%
“…In one local review, SSI postappendectomy was found in 31 patients out of 433 (7%) [ 31 ]. Our data showed SSI in 26 patients (5.8%) and deep-spaced collection identified in 13 patients (2.9%) managed by CT-guided drainage.…”
Section: Discussionmentioning
confidence: 99%
“…A great practice is earned by surgeons during the two world wars in dealing with contaminated wounds and applying DPC of such wounds after being healthy at day 3-7 following surgery was fixed [19]. Increasing the severity of the appendicitis being operated on leads to increase the rate of postoperative SSI following appendicectomy, and the majority of wound infections occurs following appendicectomy for complicated appendicitis [20]. The wounds of these dirty operations are essentially contaminated.…”
Section: Discussionmentioning
confidence: 99%